Exploring the Effect of Obscurants on Safe Landing Zone Identification - Sevcik, Keith W.; Kuntz, Noah; Oh, Paul Y. (Journal of intelligent & robotic systems, 2010)
Manned rotorcraft are often employed in harsh environments and difficult terrain that are inaccessible to other craft. Conversely, robotic rotorcraft are operated in controlled settings, often at safe, high altitudes. Missions such as cargo delivery, medevac and fire fighting are unachievable because of unpredictable adverse environmental conditions. To enable UAVs to perform these missions, the effects of obscurants on UAV sensor suites and algorithms must be clearly understood. This paper explores the use of a laser range finder to accomplish landing zone identification in unknown, unstructured environments. The ability to detect a landing zone in environments obscured by smoke is investigated. This is accomplished using a design methodology of testing and evaluating in a controlled environment followed by verification and validation in the field. This methodology establishes a concrete understanding of the sensor performance, thereby removing ambiguities in field tests.